2011
DOI: 10.1128/jvi.00071-11
|View full text |Cite
|
Sign up to set email alerts
|

Feline Tetherin Efficiently Restricts Release of Feline Immunodeficiency Virus but Not Spreading of Infection

Abstract: Innate resistance to retroviral infection and replication is induced by interferons (IFNs). IFN-inducible factors restricting viral replication include the cytidine deaminase APOBEC3G (40, 60) and the E3 ubiquitin ligase TRIM5 (1), both of which target replication primarily during the process of viral entry. A third IFN-inducible activity, tetherin (BST-2/ CD317/HM1.24), acts to restrict viral release (13,35,36,41,62). The importance of these factors in controlling viral replication is underlined by the requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 66 publications
4
85
0
Order By: Relevance
“…Therefore, because HIV-1 cannot counteract SAMHD1, it seems that, in contrast to other restriction factors, overcoming SAMHD1 is dispensable for efficient HIV-1 spread. This is in contrast, for example, to BST-2, because BST-2 nonspecifically targets the lipidic outlayer of enveloped viruses and has a broad impact on viral release [33][34][35][36][37][38][39][40][41]. Consequently, viruses have evolved distinct means to counteract this hurdle to viral budding.…”
Section: Samhd1 As An Exception?mentioning
confidence: 90%
“…Therefore, because HIV-1 cannot counteract SAMHD1, it seems that, in contrast to other restriction factors, overcoming SAMHD1 is dispensable for efficient HIV-1 spread. This is in contrast, for example, to BST-2, because BST-2 nonspecifically targets the lipidic outlayer of enveloped viruses and has a broad impact on viral release [33][34][35][36][37][38][39][40][41]. Consequently, viruses have evolved distinct means to counteract this hurdle to viral budding.…”
Section: Samhd1 As An Exception?mentioning
confidence: 90%
“…For example, the Fv-4 gene in mice encodes a full-length Env protein which closely resembles ecotropic murine leukemia virus (MLV) and confers resistance to ecotropic MLV infection by receptor interference (19,20). Host defense against retroviral infection is common, and feline APOBEC and BST-2 are known to function as retroviral restriction factors in cats (21)(22)(23). Interestingly, feline TRIM5 lacks antiretroviral activity (24).…”
mentioning
confidence: 99%
“…Cells were treated for 24 h with or without 1,000 units/ml alpha interferon (IFN-␣) (Kingfisher Biotech), and the total RNA was extracted as described above. One hundred nanograms of total RNA was subjected to reverse transcription using SuperScript II reverse transcriptase and oligo(dT) [12][13][14][15][16][17][18] as a primer (Invitrogen). Synthesized cDNAs were then subjected to real-time PCR using a SYBR green Master Mix kit (Invitrogen) according to the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Later, it was found that human tetherin has very broad antiviral activities, which also target many other enveloped viruses, including retroviruses, filoviruses, arenaviruses, paramyxoviruses, herpesviruses, and rhabdoviruses (2)(3)(4)(5)(6)(7)(8)(9). Human tetherin orthologs have been isolated from several other species, including monkey, cat, pig, mouse, cattle, and sheep, which all show similar antiviral activities (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%